Windrow Scarifier for Rotary Mower (Agricultural Engineering, 2016)
In order to accelerate the process of drying of grass mowed for hay and haylage there are numerous technological treatments: multiple tedding, raking in rolls and turning rolls, mechanical impact on green forage in the process of mowing by the use of presses and windrow scarifiers. Presently mechanical maceration of green forage with mowing is popular. Papilionaceous feed plants are subjected to windrow presses and graminacenous plants to beating working systems. Analysis of various devices for acceleration of the drying process of green forage proves that they are quite complex and expensive on account of considerable material consumption. In order to eliminate the faults in the Russian Scientific and Research Fodder Institute of Wiliams a completely different windrow scarifier for the rotary mower KR-2.4 M was developed. It has a simple structure and it serves for acceleration of field drying of mowed grass in loose rolls. The paper presents the results of the research on a mower with an experimental windrow scarifier